Recuerdos del Imperio Los ingleses en América Central (18211915) - Quesada, Rodrigo (Editorial Universidad Nacional (EUNA), 2017)
In this book, an attempt is made to make a portrait of how English diplomacy functioned in its relations with the Central American states, between the years from 1821 to 1915. It is a picture that we seek to paint with the most hidden details about participation of that English diplomacy in construction, for example, of the commercial practices with which Central America aspired to insert itself in the world market.